Optimization of FADs-based tuna fishing in the Fishing Port of Pondokdadap, East Java, Indonesia. Issue 1 (January 2020) - Damora, A; Gigentika, S; Adityarini, S; Rahmah, A; Tamanyira, M M; Nurdin, E; Wiadnya, D G R
Abstract: The Minister of Marine Affairs and Fisheries Regulation number 26/2014 has decreed that the distance between FADs should not be less than 10 nautical miles and should not be installed to make a fence effect. Highly dense FADs that are deployed with not enough distance between them in a certain period will change the movement pattern of tuna. This study aims to obtain information on the actual data of FADs deployed in the southern waters of East Java, to estimate the deployment area and to provide a recommendation on the ideal number of FADs deployed in these waters. The FAD deployment area has been estimated to be 219, 792 km 2 or 21, 979, 200 ha. Based on this estimation, it is calculated that the ideal number of FADs installed in these waters is 814 units. Estimates of the optimal number of tuna fishing units are carried out using linear goal programming (LGP) which suggests 380 units of sekoci (fishing vessel) as the optimal unit number that can operate annually at the Fishing Port of Pondokdadap, Malang Regency. The number of sekoci currently operating at this port is 644 units.